2003
DOI: 10.1038/sj.leu.2402909
|View full text |Cite
|
Sign up to set email alerts
|

Higher doses of CD34+ peripheral blood stem cells are associated with increased mortality from chronic graft-versus-host disease after allogeneic HLA-identical sibling transplantation

Abstract: Allogeneic peripheral blood stem cell transplantation (PBSCT) has emerged as an alternative to bone marrow transplantation. PBSCT can be associated with a higher incidence of chronic graft-versus-host disease (cGVHD). In this study, we investigated whether there was a correlation between the composition of PBSC grafts (CD34+ and CD3+ cells) and hematological recovery, GVHD, relapse, and relapse-free survival (RFS) after myeloablative HLA-identical sibling PBSCT. The evolution of 100 acute or chronic leukemia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
102
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 55 publications
10
102
8
Order By: Relevance
“…[17][18][19] Although no significant association between the number of infused CD3 þ cells and incidence of GVHD was found; paradoxically they showed that the more CD34 þ cells infused, the higher the incidence of cGVHD. 18,19 An explanation for this interesting finding remains a mystery. In elegant experiments, Reisner et al 20 showed that donor CD34 þ cells can act as 'veto' cells and may inactivate host T-cells, with donor alloreactivity.…”
Section: Discussionmentioning
confidence: 91%
“…[17][18][19] Although no significant association between the number of infused CD3 þ cells and incidence of GVHD was found; paradoxically they showed that the more CD34 þ cells infused, the higher the incidence of cGVHD. 18,19 An explanation for this interesting finding remains a mystery. In elegant experiments, Reisner et al 20 showed that donor CD34 þ cells can act as 'veto' cells and may inactivate host T-cells, with donor alloreactivity.…”
Section: Discussionmentioning
confidence: 91%
“…While some studies have suggested that high doses of CD34 þ cells are associated with a greater likelihood of chronic GVHD, our data suggest that other factors may be more important since the risk of chronic GVHD was high within GM-CSF group despite the fact that they received a relatively modest median CD34 þ cell dose (3.1 Â 10 6 /kg). 10,38,39 Despite the fact that the cohort of donors receiving combination G/GM-CSF mobilized the greatest numbers of CD34 þ cells without significant additive toxicity, this did not translate into any clear clinical advantages to the recipients as the rate of hematopoietic engraftment, incidence of chronic GVHD, risk of relapse, and overall likelihood of survival did not differ significantly from the G-CSF alone group. In fact, the risk of acute GVHD was greatest in this combination group.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Nevertheless, in only a minority of the randomized comparative trials did this translate into an overall survival advantage and some studies suggested the use of G-CSF mobilized PBPC was associated with a greater risk of either acute or chronic graft-versus-host disease (GVHD), or both. 6,[8][9][10] In two recent retrospective studies in patients with aplastic anemia or children with leukemia performed by the International Bone Marrow Transplant Registry, transplantation of G-CSF mobilized PBPC was associated with higher rates of GVHD. 11,12 Therefore, strategies to limit GVHD following PBPC transplantation are necessary.…”
Section: Csf; G-csfmentioning
confidence: 99%
“…Previous studies found a greater incidence of extensive chronic GVHD in recipients of a higher CD34 + dose after PBSCT. 17,18 However, in our pediatric cohort a higher CD34 + dose resulted only in the salutary effect of decreasing relapse and improving survival without increasing the risk for either acute or chronic GVHD. One factor that we believe is key to the lack of association between cell dose and GVHD was the use of rabbit ATG (2.5 mg/kg per day for 3 days) during conditioning before transplant.…”
Section: Discussionmentioning
confidence: 98%